Beberapa Menu Sarapan Menggunakan Pangan Lokal Terhadap Pemenuhan Kebutuhan Gizi Siswa Sekolah Dasar - Henry S. Imbar; Vera Harikedua; Rivolta Walalangi (Jurnal GIZIDO, 2018)
Organoleptic testing is a test that is based on sensing process. Sensing can also mean mental reactions (sensation) if the senses receive stimuli (stimulus). Reaction or impression that is caused due to the stimulation may be an attitude to toward or away from, liking or disliking objects will cause stimulation.Formulation of the problem in this research is how the acceptance and preference level of primary school students towards some kind of breakfast menu using local food in North Sulawesi in order to fulfill nutritional needs.The general objective of this study is to make local food in North Sulawesi as a basic ingredient in making a breakfast menu with a variety favored by children in order to fulfill the nutritional needs of elementary school. The benefits of this research provide understanding to the community in particular who have children of primary school age that the fulfillment of nutrients on elementary school children is not always synonymous with foodstuffs are expensive, must be imported, instant, branded, but the quality and nutritional content is not very relevant to the needs child nutrition. This type of research is quasy Experiment was conducted in a laboratory study Culinary Nutrition Poltekkes Kemenkes Manado and Elementary School 06, which is located in Manado City. Collecting data in this study is the result of tests performed on the organoleptic properties, which consist of preference for appearance, flavor, texture, color and aroma.Hedonic data processing using Kruskal Wallis test showed no significant difference from the third menu tested. Conclusion statistically no significant difference between the three breakfast menu with a conventional menu, but based on the average value of the hedonic score differences.